2003
DOI: 10.1095/biolreprod.102.012583
|View full text |Cite
|
Sign up to set email alerts
|

Human Feeder Layers for Human Embryonic Stem Cells1

Abstract: Human embryonic stem (hES) cells hold great promise for future use in various research areas, such as human developmental biology and cell-based therapies. Traditionally, these cells have been cultured on mouse embryonic fibroblast (MEF) feeder layers, which permit continuous growth in an undifferentiated stage. To use these unique cells in human therapy, an animal-free culture system must be used, which will prevent exposure to mouse retroviruses. Animal-free culture systems for hES cells enjoy three major ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
243
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(256 citation statements)
references
References 14 publications
(26 reference statements)
7
243
0
4
Order By: Relevance
“…Li et al indicated that homologous somatic cells from monkey could support the growth of monkey ES cells regardless of the tissue from which the feeder cells were derived [33]. In humans, some studies also indicated that cells from the foreskin [13] or adult Fallopian tube epithelium [14] could support the propagation and self-renewal of hES cells. These cells not only support the growth of ES cells, but also enable the formation of ICM outgrowths and the derivation of ES cells with a similar efficiency to mouse feeder cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al indicated that homologous somatic cells from monkey could support the growth of monkey ES cells regardless of the tissue from which the feeder cells were derived [33]. In humans, some studies also indicated that cells from the foreskin [13] or adult Fallopian tube epithelium [14] could support the propagation and self-renewal of hES cells. These cells not only support the growth of ES cells, but also enable the formation of ICM outgrowths and the derivation of ES cells with a similar efficiency to mouse feeder cells.…”
Section: Discussionmentioning
confidence: 99%
“…The normal characteristics of hES cells can be maintained using a feeder-free culture system, and successful derivation has been reported using this system [11,12], however, this system has not yet been applied widely because of its complexity and associated difficulties. Feeder cells from human tissues, including foreskin fibroblasts [13] and adult Fallopian tube epithelial cells [14], have been used to derive and culture hES cells, and all of these types of feeder cell can support the prolonged undifferentiated growth of hES cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Diff Miz-hES6 feeder cells support the proliferation of hESCs as efficiently as MEFs. In contrast, the literature suggests hESCs cultured on other human feeder cells require a 5-7 day passaging interval (data not shown) (Richards et al, 2002;Amit et al, 2003a;Cheng et al, 2003;Hovatta et al, 2003;Lee et al, 2005). The hESC lines cultured on Diff Miz-hES6 feeder cells were relatively circular in shape (Figure 2), which is similar to their morphology when cultured on MEF feeder cells (data not shown).…”
Section: Long-term Support Of Hesc Growth On Diff Miz-hes6 Feeder Cellsmentioning
confidence: 85%
“…Recently, we and other groups demonstrated that it is possible to culture hESCs on feeder cells that originate from human sources (Richards et al, 2002;Amit et al, 2003a;Cheng et al, 2003;Hovatta Efficient culture system for human embryonic stem cells using autologous human embryonic stem cell-derived feeder cells Lee et al, 2005). In most cases, however, these human feeder cell lines are derived from samples obtained from patients or discarded human fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, regardless of the isolation method used, some groups have come to the general conclusion that cells grown on mouse feeder cells would not be appropriate for clinical applications, and this has lead to significant efforts to grow ESC lines on human feeders [17], immortalized cells [18], feeder cell lines that have been derived from the original ESC themselves [19] and the culture on Matrigel TM [20]. We obtained better adhesion rates when we used the MEF instead of the gelatin growth surface using the laser drill (80 versus 27.3 %).…”
Section: Discussionmentioning
confidence: 99%